Molecular Breeding for Sustainable Crop Improvement Volume 2 - Rajpal, Vijay Rani; Rao, S. Rama; Raina, S.N (Sustainable Development and Biodiversity,, 2016)
Molecular Breeding for Sustainable Crop Improvement, Volume 2 focuses on integration of advances in genetics, cytogenetics, molecular biology and biotechnology aimed at alien gene introgression for genetic improvement of major crop species at molecular level to help overcome the limitations associated with conventional plant breeding. This book includes articles on the availability and application of modern genomic approaches, tools, and resources in a precision breeding approach. The contributions involve the use of molecular markers and linkage, QTL and association mapping of agronomic traits to identify candidate genes and to design functional markers for marker assisted selection (MAS), gene pyramiding using MAS coupled with marker assisted back cross breeding (MABB), next generation sequencing (NGS) to generate genome wide markers and screen new alleles, and targeting induced local lesions in genomes (TILLING) or ecotype TILLING (EcoTILLING) for the screening of either mutant or natural germplasm collections to integrate genomic information into directional and selective breeding in crops to maximize genetic gains. Breeders, taxonomists, geneticists, cytogeneticists, molecular biologists and biotechnologists are going to greatly benefit from this book. We sincerely hope that this book will serve as a milestone in the precision breeding of crops to achieve meaningful plant genetic improvement.